Comparative evaluation of the effect of the substrate thickness and inherent process defects on the static and fatigue performance of FSW and adhesive-bonded overlap-joints in an AA6016 alloy. (April 2021) - Lertora, Enrico; Campanella, Davide; Pizzorni, Marco; Mandolfino, Chiara; Buffa, Gianluca; Fratini, Livan
Abstract: This work aims at evaluating the mechanical performance of joints in an AA6016 alloy, manufactured by means of two alternative processes: friction stir welding and adhesive bonding. Given its wide use in industrial fields such as automotive and aeronautics, an overlap configuration of joints was selected for the study, and a specific method based on the overlap length evaluation has been developed to allow comparisons among the cases. Two substrate thicknesses are considered in order to vary the overall joint stiffness, and the effect of such geometrical parameter on the mechanical behavior of the joined system is experimentally investigated. The experimental findings highlight that the stiffness of the joint may emphasize the effect of inherent defects due to process, severely affecting the mechanical and failure behavior of overlap-configured joints under static- or cyclic-load conditions.